Analysis of studies reporting gender differences in shopping addiction - Kaylı, Derya Şaşman; Özlem, Şevval Özge (Journal of Dependence, 2022)
This study aims to examine the year and method characteristics of the researches in the field of shopping addiction in the international literature, how the areas related to shopping addiction diversify, how they differ on the basis of gender, with which variables the scope of the subject is discussed and to determine the trend in this direction. Qualitative method and purposive sampling technique were used in the study. Research articles made in the international literature between 2010-2021 were scanned through Google Scholar and subjected to descriptive analysis. As a result of the analysis, a total of 65 studies, including qualitative, quantitative and mixed patterns, were identified and 18 studies were included in the study the scope of the inclusion criteria. According to the research findings, quantitative research method is frequently preferred in studies; it was prepared in a survey research design and with an appropriate sampling model; it is seen that is it mostly carried out with undergraduate students, the data are collected with the scales used in the field and analyzed by the correlation method. In addition, it has been determined that shopping addiction is mostly handled on the basis of self-esteem, body image and gender differences. As a sample group, it was revealed that the number of female participants in the studies was higher than the number of male participants. It is seen that the quantitative method is widely used in the field of shopping addiction. However, qualitative or mixed-patterned studies are needed in order to discuss in depth what patterns the subjects is intertwined with and what meanings it has. On the other hand, it is seen that women come to forefront as a risk group in studies in the field of shopping addiction. To understand why and how risk factors differ on the basis of genders, there is a need to establish relevant intervention methods. There is a need to carry out studies in which other addictions accompanying shopping addiction are taken into account.